Association Between Nutritional Status and Anemia Incidence Among High School Adolescent Girls - Sitti Rahmah Mustakin; Adriyani Adam (Indonesian Journal Publisher, 2026)
Anemia remains a critical global health issue among adolescent girls, often theoretically linked to underweight nutritional status; however, the phenomenon of hidden hunger indicates that micronutrient deficiencies are not always reflected in anthropometric parameters, thus the actual correlation between nutritional status and anemia incidence needs to be empirically demonstrated. This study aimed to analyze the relationship between nutritional status and the incidence of anemia among adolescent girls at SMA Negeri 20 Pangkep. This observational analytic study employed a cross-sectional design and was conducted in December 2025. A total of 92 adolescent girls from grades X-XII were selected using the total sampling technique. Data were collected through anthropometric measurements to determine Body Mass Index for Age (BMI-for-Age) and capillary hemoglobin testing using a POCT device, then analyzed using the Chi-Square test (α = 0.05). The findings revealed an anemia prevalence of 23.9%, classifying it as a significant public health problem. Statistical analysis showed that the proportion of anemia in underweight adolescent girls (31.3%) was not significantly different compared to adolescent girls with normal nutritional status (22.4%). The bivariate test confirmed no significant relationship between nutritional status and the incidence of anemia (р = 0.449). Macro-nutritional status (BMI) is not a primary determinant of anemia in this population, implying that adolescent girls with proportional bodies share an equal risk of iron deficiency; therefore, anemia prevention programs and Iron Supplementation Tablet (TTD) distribution must target all adolescent girls evenly, accompanied by continuous education.